Redefining the Guillain-Barré Spectrum in Children: Neuroimaging Findings of Cranial Nerve Involvement - Zuccoli, G.; Panigrahy, A.; Bailey, A.; Fitz, C. (American Journal of Neuroradiology, 2011)
SUMMARY: GBS and its MFS variant are acute polyneuropathies that are considered to represent a continuum rather than distinct entities, due to the overlap in their clinical features. Enhancement of the CE roots represents the neuroradiologic hallmark of GBS, while findings of neuroimaging studies in MFS are usually unremarkable. Our purpose was to evaluate the MR imaging findings of polyneuropathy in 17 children affected by GBS and its MFS variant. Fourteen of our 17 patients demonstrated CE enhancement, with predominant involvement of the anterior roots. Of 6 patients who underwent MR imaging of the brain, 5 had cranial nerve involvement. In children affected by GBS-MFS, involvement of the CE roots may be considered part of a more extensive autoimmune neuropathy, as demonstrated by enhancement of cranial nerves. Brain MR imaging should be considered in the routine evaluation in pediatric patients with GBS-MFS for the evaluation of the cranial nerves. CEcauda equinaGBSGuillain-Barré SyndromeMFSMiller Fisher syndrome